Health behaviors in geriatric patients with hypertension in the light of empirical studies - Zielińska-Więczkowska, Halina; Pawelska, Katarzyna; Muszalik, Marta; Kędziora-Kornatowska, Kornelia; Kornatowski, Tomasz (Nursing in the 21st Century, 2011)
Aim. The aim of the study was to assess health behaviors of geriatric patients with arterial hypertension with relation to socio-demographic factors. Material and methods. The study included 85 elderly patients hospitalized in Geriatric Clinic between December 2009 and April 2010. The main criterion for inclusion was arterial hypertension. The study was performed using diagnostic survey method and original assessment tool. The consent of the Bioethical Commission of NCU Toruń, CM Bydgoszcz was obtained as well as written consent of each patient. Results. Health behaviors of geriatric patients with hypertension differ and depend on the place of residence, education level and slightly less by gender. Women, people who live in big cities and those with higher level of education have a greater tendency toward health behaviors. Conclusions. 1. In the process of educating patients with hypertension, more attention should be paid to less educated people, those living in a village and men. 2. Elderly people with hypertension have difficulties with taking care for health, proper eating habits and physical activity.